Examining the Job Flexibility Explanation for the Gender Wage Gap in the U.S. - Westenberg, Joseph M.; Schaffer, David L. (My University, 2017)
In recent research, some economists have suggested that most of the remaining gap in wages between men and women in the U.S. can be explained by the fact that women choose more time-flexible, and therefore, lower paid jobs than men. These jobs pay less because workers are less productive in jobs with greater time flexibility. Therefore, women are voluntarily sorting in to these jobs and their overall lower pay is not caused by any type of gender discrimination. In fact then, there may be no further need for equal pay and affirmative action public policies in regards to gender. In our study, we address this one major question: does the data support this Time Flexibility Hypothesis? We analyze the data using a variety of statistical techniques, and find only weak support for this theory.
Color poster with text, images, graphs, and tables.
Keywords: Gender discrimination; Female workers; Gender wage gap; Time flexibility hypothesis; Posters